2021
DOI: 10.1002/ece3.7549
|View full text |Cite
|
Sign up to set email alerts
|

Differential reliance on aquatic prey subsidies influences mercury exposure in riparian arachnids and songbirds

Abstract: Cross-ecosystem nutrient subsidies are important components of ecosystem function (Polis et al., 1997). Lotic ecosystems, in particular, receive substantial allochthonous nutrient input from riparian leaf litter and detritus, and in return contribute nutrients and energy back to the surrounding riparian areas via aquatic insect emergence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Elevated THg concentrations in emerging aquatic insects (581–1175 ng THg g −1 dry wt) only measured downstream of mining also led to high adult aquatic insect‐mediated fluxes of THg (16.3 ng m −2 day −1 on average). The concentrations found in adult aquatic insects downstream of mining fell within the range of those reported for adult aquatic insects emerging from hydroelectric reservoirs (140–1500 ng THg g −1 dry wt; Tremblay et al, 1998), but were higher than those reported from streams in New Hampshire (USA; Chaves‐Ulloa et al, 2016), streams in the southern Finger Lakes region (NY, USA; Twining et al, 2021), the Willamette River (OR, USA; A. K. Jackson et al, 2021), the Upper Mississippi River (USA; Dukerschein et al, 1992), and the Buffalo Area of Concern in the contaminated Buffalo River (NY, USA; Pennuto & Smith, 2015). As a result, the adult aquatic insect‐mediated flux of THg downstream of mining was almost double that reported from seminatural fishless experimental ponds (less than 7 ng MeHg m −2 day, converted to less than 8.8 ng THg m −2 day following Chaves‐Ulloa et al, 2016; also see Tweedy et al, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…Elevated THg concentrations in emerging aquatic insects (581–1175 ng THg g −1 dry wt) only measured downstream of mining also led to high adult aquatic insect‐mediated fluxes of THg (16.3 ng m −2 day −1 on average). The concentrations found in adult aquatic insects downstream of mining fell within the range of those reported for adult aquatic insects emerging from hydroelectric reservoirs (140–1500 ng THg g −1 dry wt; Tremblay et al, 1998), but were higher than those reported from streams in New Hampshire (USA; Chaves‐Ulloa et al, 2016), streams in the southern Finger Lakes region (NY, USA; Twining et al, 2021), the Willamette River (OR, USA; A. K. Jackson et al, 2021), the Upper Mississippi River (USA; Dukerschein et al, 1992), and the Buffalo Area of Concern in the contaminated Buffalo River (NY, USA; Pennuto & Smith, 2015). As a result, the adult aquatic insect‐mediated flux of THg downstream of mining was almost double that reported from seminatural fishless experimental ponds (less than 7 ng MeHg m −2 day, converted to less than 8.8 ng THg m −2 day following Chaves‐Ulloa et al, 2016; also see Tweedy et al, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…An effective fine-scale sentinel requires a defined route of exposure, insensitivity to the pollutant, and tissue concentrations that correspond to ambient concentrations consistently across space and time (Beeby, 2001). The tetragnathid and araneids collected in the present study have high proportions of adult aquatic insects in their diet (Akamatsu & Toda, 2011;Jackson et al, 2021;Raikow et al, 2011); have historically been found near areas with high levels of persistent contaminants, with no observed adverse effects (Chumchal et al, 2022); and integrate contaminant signals at small spatial scales (<100 m) for a wide variety of organic contaminants including PCBs, per-and polyfluoroalkyl substances, pharmaceuticals, and endocrine disruptors (Koch et al, 2021;Previsǐcé t al., 2021;Richmond et al, 2018;Walters et al, 2008). We demonstrated that spider tissues reflect sediment PCDD/F homolog distributions as well as homolog concentrations along a PCDD/F homolog contamination gradient.…”
Section: Discussionmentioning
confidence: 92%
“…Contaminants have complex effects on communities and food webs in linked aquatic‐terrestrial ecosystems (Clements et al, 2016; Jackson et al, 2021; Kraus et al, 2020; Schiesari et al, 2018). Compounds that are toxic to organisms at the base of the food web can lead to changes in consumer diets or loss of consumer biomass.…”
Section: Introductionmentioning
confidence: 99%